Dynamic physical education for secondary school students - Pangrazi, Robert P.; Darst, Paul W. (Boston : Allyn and Bacon, 1997)
This book is divided into five sections: Justifying a Physical Education Program; Designing a Physical Education Program; Teaching a Physical Education Program; Developing a Total Program; Implementing Instructional Activities.
Keywords: Constructivism; Physical education for children; Physical education techers; Physical education and training -- Study and teaching (Secondary) -- United States; Physical education and training -- United States -- Curricula; Physical education and training -- Study and teaching (Secondary) -- Canada